Microstructure and Tribological Characteristics of Strain-Induced Melt Activation (SIMA)-Processed Al–10Cu–Fe alloy - Sankara Rao L.; Jha A.K.; Ojha S.N. (My University, 2025)
In the present study, the influence of synthesis methods, namely the conventional metal mould casting (MMC) and strain-induced melt activation (SIMA) processes, on the microstructure and tribological characteristics of Al–10Cu–Fe alloy has been studied. The alloy was prepared by melting the commercial purity aluminium and copper. The effect of holding time in semi-solid region on the microstructure of the alloy subjected to SIMA was studied. Microstructural characterization was performed using optical and scanning electron microscopy, while chemical segregation is investigated using energy-dispersive spectroscopy. Hardness and strength of the resulting alloy are measured using macroindentation and tensile testing, respectively. Near-spherical grains were achieved in the SIMA process with an average grain diameter varying from 44 to 67 µm for holding times ranging from 30 to 55 min. The wear properties of stirred MMC alloy which was subjected to SIMA process are considerably better than those of either conventional MMCs or unstirred MMC subjected to SIMA process. The 50% pre-deformation followed by intercritical annealing at 580 °C and 30 min holding time is the optimum parameters to obtain the wear properties of Al–10Cu–Fe alloy. The improved wear and mechanical properties of the alloy are discussed in the light of the microstructural features of SIMA-processed alloy and the nature of the worn surfaces. © 2017, American Foundry Society.